2016
DOI: 10.17221/324/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of selenium biofortification of winter wheat grain

Abstract: Selenium (Se) is one of the elements that determine the normal functioning of an organism; it has antioxidant properties and protects the organism against the actions of free radicals and carcinogenic factors. Selenium is an element that fulfils an important physiological function (Kieliszek and Blažejak 2013), but apart from all the elements, selenium has one of the narrowest range between dietary deficiency (< 40 µg/day) and toxic levels (> 400 µg/day) (Fordyce 2007).While there is no evidence of Se need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
2
27
0
1
Order By: Relevance
“…Similarly, our earlier rice field trials showed that the Se concentration in brown rice was approximately two times higher in the Se(VI) treatment than in the Se(IV) treatment ( Deng et al., ). In wheat, the recovery efficiency of Se(IV) and Se(VI) in grains were 1.4–1.5% and 13.2–15.1% of the applied Se, respectively ( Ducsay et al., ). And in carrots, Kápolna et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, our earlier rice field trials showed that the Se concentration in brown rice was approximately two times higher in the Se(VI) treatment than in the Se(IV) treatment ( Deng et al., ). In wheat, the recovery efficiency of Se(IV) and Se(VI) in grains were 1.4–1.5% and 13.2–15.1% of the applied Se, respectively ( Ducsay et al., ). And in carrots, Kápolna et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our earlier rice field trials showed that the Se concentration in brown rice was approximately two times higher in the Se(VI) treatment than in the Se(IV) treatment . In wheat, the recovery efficiency of Se(IV) and Se(VI) in grains were 1.4-1.5% and 13.2-15.1% of the applied Se, respectively (Ducsay et al, 2016). And in carrots, Ká polna et al (2009) showed that after foliar spraying with Se, the Se concentration in leaves was 60% higher in the Se(VI) compared to the Se(IV) treatment.…”
Section: Selection Of An Optimal Se Source and Spraying Date For Se Fmentioning
confidence: 98%
“…Studies also showed that selenate usually has higher bioavailability than selenite in grain crops or vegetables. Ducsay et al . found that the Se recovery was approximately ten‐fold higher for selenate spray than selenite spray in wheat grains.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also showed that selenate usually has higher bioavailability than selenite in grain crops or vegetables. Ducsay et al 24 found that the Se recovery was approximately ten-fold higher for selenate spray than selenite spray in wheat grains. Kápolna et al 5 reported that the Se concentration in carrot leaves treated with selenate was approximately 16-fold higher than that treated with selenite.…”
Section: Effects Of Se Spray On Se Enrichment In Blueberrymentioning
confidence: 99%
“…An alternative complimentary solution to mineral malnutrition is "biofortification." Biofortification has been defined as the process of increasing the bioavailable concentrations of essential elements in edible portions of crop plants through agronomic intervention or genetic selection [3][4][5]. e concept of biofortification is attractive not only for improving the growing conditions of crops but also for exploiting a plant's potential for nutrient mobilization and utilization.…”
Section: Introductionmentioning
confidence: 99%